2021
DOI: 10.1055/s-0041-1731033
|View full text |Cite
|
Sign up to set email alerts
|

A Volumetric Study of the Corpus Callosum in the Turkish Population

Abstract: Objective The aim of this study is to measure the average corpus callosum (CC) volume of healthy Turkish humans and to analyze the effects of gender and age on volumes, including the genu, truncus, and splenium parts of the CC. Patients and Methods Magnetic resonance imaging brain scans were obtained from 301 healthy male and female subjects, aged 11 to 84 years. The median age was 42 years (min–max: 11–82) in females and 49 years (min–max: 12–84) in males. Corpus callosum and its parts were calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…However, this study supports the longitudinal study of Giedd et al due to the similar increase rate of CC's development segments (Giedd et al, 1999). Soysal et al investigated CC volume in a wide age range with MRICloud in a recent study (Soysal et al, 2022). The CC median value they found in the 11–29 age range was close to the mean value for the 11–18 age range of our study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, this study supports the longitudinal study of Giedd et al due to the similar increase rate of CC's development segments (Giedd et al, 1999). Soysal et al investigated CC volume in a wide age range with MRICloud in a recent study (Soysal et al, 2022). The CC median value they found in the 11–29 age range was close to the mean value for the 11–18 age range of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Soysal et al examined the volumetric status of CC with MRICloud in 11‐84‐year‐olds. They found that the volumes of both total CC and subregions of CC were significantly greater in males (Soysal et al, 2022). This study's mean CC volume values of the 11–18 age group were very close to the 11–29 age group of Soysal et al Therefore, we think sexual dimorphism is not caused by the immature CC period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations